A Facet‐Specific Quantum Dot Passivation Strategy for Colloid Management and Efficient Infrared Photovoltaics. Issue 17 (12th March 2019) - Kim, Younghoon; Che, Fanglin; Jo, Jea Woong; Choi, Jongmin; García de Arquer, F. Pelayo; Voznyy, Oleksandr; Sun, Bin; Kim, Junghwan; Choi, Min‐Jae; Quintero‐Bermudez, Rafael; Fan, Fengjia; Tan, Chih Shan; et al.
Abstract: Colloidal nanocrystals combine size‐ and facet‐dependent properties with solution processing. They offer thus a compelling suite of materials for technological applications. Their size‐ and facet‐tunable features are studied in synthesis; however, to exploit their features in optoelectronic devices, it will be essential to translate control over size and facets from the colloid all the way to the film. Larger‐diameter colloidal quantum dots (CQDs) offer the attractive possibility of harvesting infrared (IR) solar energy beyond absorption of silicon photovoltaics. These CQDs exhibit facets (nonpolar (100)) undisplayed in small‐diameter CQDs; and the materials chemistry of smaller nanocrystals fails consequently to translate to materials for the short‐wavelength IR regime. A new colloidal management strategy targeting the passivation of both (100) and (111) facets is demonstrated using distinct choices of cations and anions. The approach leads to narrow‐bandgap CQDs with impressive colloidal stability and photoluminescence quantum yield. Photophysical studies confirm a reduction both in Stokes shift (≈47 meV) and Urbach tail (≈29 meV). This approach provides a ≈50% increase in the power conversion efficiency of IR photovoltaics compared to controls, and a ≈70% external quantum efficiency at their excitonic peak. Abstract : A novel solution‐phase ligand exchange is reported whereby (100) and (111) facets are selectively passivated by sodium and lead‐halides, respectively. This approach enables realization of narrow‐bandgap colloidal quantum dots with improved colloidal stability and photophysical properties. This facet‐specific passivation significantly increases infrared solar cell performance, leading to a 50% increase in power conversion efficiency compared to conventional lead‐halide‐only passivation.